Hydrogeologic Considerations In Mining And Development Of Energy Resources, San Juan Basin, New Mexico - Introduction - General Statement - William J. Stone (Society for Mining, Metallurgy & Exploration, 1976)
Large reserves of coal and uranium exist in the San Juan Basin of northwestern New Mexico. The mining and development of these resources necessarily also involves depletion of area water resources and disturbance of the hydrogeologic framework. In an effort to better define the water resources and hydrogeologic framework of this region, the New Mexico Bureau of Mines and Mineral Resources, the U. S. Geological Survey, and the State Engineer's Office are presently engaged in a cooperative study of the Hydrogeology and Ground-Water Resources of Northwestern New Mexico. The purposes of this paper are to introduce our project, review tine coal and uranium resources of the San Juan Basin, and discuss the various hydrogeologic considerations recognized in their exploitation.